The World Bank's lawyers : the life of international law as institutional practice - Meerssche, Dimitri van den (Oxford : Oxford University Press, 2022)
'The World Bank's Lawyers' gives an original socio-legal account of the evolving institutional life of international law. It tells the previously untold story of the World Bank's legal department. This is a story of people and the practices they cling to and how these practices gain traction, or fail to do so, in an international bureaucracy.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: World Bank. -- Legal Department -- History; International law; Law; International law